Аллюзии на елизаветенский театр в трагедии У. Шекспира «Гамлет» - Арутюнян, А.Г.; Полховская, Е.В. (Культура народов Причерноморья, 2014)
Представленная статья посвящена рассмотрению темы «Шекспировские аллюзии на
театральные реалии» на материале его знаменитого произведения «Гамлет». Автор вводит понятие
«аллюзия», выявляет и анализирует аллюзии на елизаветинский театр в пьесе Шекспира «Гамлет», а
также представляет выводы относительно трактовки Шекспиром темы театра. Новизна данной
работы состоит в использовании новой методики, в частности, метода интертекстуального и
текстового анализа. В работе использованы общие и частные методы исследования, в том числе,
метод стилистического анализа, типологический и культурно-исторический подходы. Проблема
данного исследования носит актуальный характер в наше время. Дана стаття присвячена розгляду теми «Шекспірівські алюзії на театральні реалії» на
матеріалі його знаменитого твору «Гамлет». Автор вводить поняття «алюзія», виявляє і аналізує
алюзії на єлизаветинський театр у п'єсі Шекспіра «Гамлет», а також представляє висновки щодо
трактування Шекспіром теми театру. Новизна даної роботи полягає у використанні нової методики,
зокрема, методу інтертекстуального й текстового аналізу. У роботі використані загальні та приватні
методи дослідження, в тому числі, метод стилістичного аналізу, типологічний та культурно-
історичний підходи. Проблема даного дослідження носить актуальний характер в наш час. The resented article is devoted to the theme «Shakespeare allusions to theatrical realias» on the basis
of his famous work «Hamlet». The author introduces the definition of allusion, identifies and analyzes the
allusions to the theater in Shakespeare's «Hamlet», and draws conclusions about Shakespeare’s understanding
of the theatre. The novelty of this work lies in the usage of a new technique, in particular, the method of
intertextual and textual analysis. We used the general and specific research methods, including the method of
stylistic analysis, typological and cultural-historical approaches. The problem of this study is of current
importance at present.
The author shows us that Hamlet has relevance in every age. It reveals not only important aspects of Hamlet’s
Denmark or Shakespeare’s England, but also today’s society. Moreover, the author comes to a conclusion that
Hamlet affords opportunities to appraise the nature of society in our own time as well as in Shakespeare’s.